2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2019
DOI: 10.1109/cvpr.2019.00470
|View full text |Cite
|
Sign up to set email alerts
|

SelFlow: Self-Supervised Learning of Optical Flow

Abstract: We present a self-supervised learning approach for optical flow. Our method distills reliable flow estimations from non-occluded pixels, and uses these predictions as ground truth to learn optical flow for hallucinated occlusions. We further design a simple CNN to utilize temporal information from multiple frames for better flow estimation. These two principles lead to an approach that yields the best performance for unsupervised optical flow learning on the challenging benchmarks including MPI Sintel, KITTI 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
311
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(311 citation statements)
references
References 40 publications
0
311
0
Order By: Relevance
“…SegFlow [40] trains an optical flow network and an image segmentation network jointly to improve the accuracy of both networks. DDFlow [41] and SelFlow [42] employ two data distillation methods and train the networks in an ''teacher-student'' manner. Although unsupervised algorithms have the advantage of not requiring labeled data, they often have complex training steps and lower accuracy than supervised methods.…”
Section: Cnn-based Optical Flowmentioning
confidence: 99%
“…SegFlow [40] trains an optical flow network and an image segmentation network jointly to improve the accuracy of both networks. DDFlow [41] and SelFlow [42] employ two data distillation methods and train the networks in an ''teacher-student'' manner. Although unsupervised algorithms have the advantage of not requiring labeled data, they often have complex training steps and lower accuracy than supervised methods.…”
Section: Cnn-based Optical Flowmentioning
confidence: 99%
“…The statistics for these two sets are shown in Fig. 7(d) and (e), where it can be observed that Table 2: The evaluation results on the KITTI flow benchmarks, where DDFlow [18], UnFlow [17], Flow2Stereo [45] and SelFlow [19] are the state-of-the-art self-supervised approaches. Best results are shown in bold font.…”
Section: Atg-pvd Datasetmentioning
confidence: 99%
“…Evaluation Since our ATG-PVD dataset does not contain optical flow ground truth, we evaluate our proposed SwiftFlow on the KITTI flow 2012 [46] and 2015 [44] benchmarks. According to the online leaderboard of the KITTI flow benchmarks, as shown in Table 2, our SwiftFlow ranks 24th on the KITTI flow 2012 3show the optical flow estimations and the corresponding error maps of (1) UnFlow [17], (2) SelFlow [19] and 3our SwiftFlow, respectively. Significantly improved regions are highlighted with green dashed boxes.…”
Section: Evaluation Of Swiftflowmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their performance in challenging regions, such as partially occluded or texture-less regions, is often unsatisfactory [10,13]. The underlying cause of this performance degradation is threefold: 1) The popular coarse-to-fine framework [12,13] is often sensitive to noises in the flow initialization from the preceding pyramid level, and the challenging regions can introduce errors in the flow estimations, which in turn propagate to subsequent levels.…”
Section: Introductionmentioning
confidence: 99%